2016
DOI: 10.1136/ejhpharm-2015-000818
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of antibiotic usage for gastrointestinal disorders in a tertiary care hospital

Abstract: Objective To assess antibiotic usage in gastrointestinal disorders with respect to appropriateness, pattern of resistance, and incidence of adverse drug reactions (ADRs). Methodology Antibiotic prescribing in the gastroenterology department of a tertiary care hospital was evaluated using the Gyssens criteria and also by assessing drug related problems (DRPs) using the Pharmaceutical Care Network Europe V.6.2. A total of 173 patients were studied prospectively by a team of clinical pharmacists. Antibiotic susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…23 A similar review conducted on antibiotics and the mechanism of resistance to the antibiotic may cause community-acquired and nosocomial infection the appropriate indications, appropriate dosage, and proper guidance should be implemented as reported by Cesurs. 24 A similar study reported and concluded that due to increased use of antibiotics causes resistance which is concluded by Odonkors et al 25 A similar study on antibiotic misuse in hospitals, and outpatient, checking whether the drug is truly indicated in a particular scenario and whether the correct choice of dosage and route of administration prescribed is appropriate has been reported by Ashrat et al 26 In a similar study on the risk associated with antibiotic overuse and reducing the problem, an increased mortality rate has been suggested by Clor et al 27 As the contraindicated to the study due to shortage of doctors, unlicensed medical providers in India the patient themselves participating in the decision to treat an illness with antibiotics has been concluded by Barker et al 28 A similar study conducted on the appropriateness of antibiotic usage was appropriate in 50% of patients and inappropriate in 50% of patients due to incorrect choices they result in different drug-related problems and adverse drug reaction has been reported by Madhu et al 29 A similar study conducted that associated the adverse event with antibiotic use and the usage of antibiotics play a critical role when used appropriately and misuse may lead to mortality has been reported by Tomma et al 30 Similar to a study conducted on evidence-based practice in the use of antibiotics of non-evidence-based prescription of antibiotics and overuse of antibiotics. Is similar to a previous study conducted by Pranita.…”
Section: Discussionmentioning
confidence: 97%
“…23 A similar review conducted on antibiotics and the mechanism of resistance to the antibiotic may cause community-acquired and nosocomial infection the appropriate indications, appropriate dosage, and proper guidance should be implemented as reported by Cesurs. 24 A similar study reported and concluded that due to increased use of antibiotics causes resistance which is concluded by Odonkors et al 25 A similar study on antibiotic misuse in hospitals, and outpatient, checking whether the drug is truly indicated in a particular scenario and whether the correct choice of dosage and route of administration prescribed is appropriate has been reported by Ashrat et al 26 In a similar study on the risk associated with antibiotic overuse and reducing the problem, an increased mortality rate has been suggested by Clor et al 27 As the contraindicated to the study due to shortage of doctors, unlicensed medical providers in India the patient themselves participating in the decision to treat an illness with antibiotics has been concluded by Barker et al 28 A similar study conducted on the appropriateness of antibiotic usage was appropriate in 50% of patients and inappropriate in 50% of patients due to incorrect choices they result in different drug-related problems and adverse drug reaction has been reported by Madhu et al 29 A similar study conducted that associated the adverse event with antibiotic use and the usage of antibiotics play a critical role when used appropriately and misuse may lead to mortality has been reported by Tomma et al 30 Similar to a study conducted on evidence-based practice in the use of antibiotics of non-evidence-based prescription of antibiotics and overuse of antibiotics. Is similar to a previous study conducted by Pranita.…”
Section: Discussionmentioning
confidence: 97%
“…The demographic characteristics of the patients show that more male patients were admitted to the surgical wards in both stages of the study, which is mirrored in other studies conducted in other countries. 28 , 29 The patients in the ASP stage had a higher mean age compared to those in the baseline stage which may have clinical implications in that older patients may have a higher risk of having other comorbidities, complications or severity of disease. Previous studies in surgical settings conducted in Malaysia and Jordan reported average ages of between 43 and 51 years, 6 , 30 respectively, which is similar to those reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other developing countries such as India and Malaysia have also shown a high percentage (39% – 42%) of inappropriate antibiotic usage. 7 , 29 However, this is not limited to developing countries, a Swiss study using Gyssens’ algorithm found a total of 32% of all prescriptions to be inappropriate which was high (37%) in patients who received antibiotics as treatment compared to those who received it for prophylaxis (17%). 37 In the Netherlands, 16% – 29% of all antibiotic prescriptions were judged inappropriate using Gyssens’ algorithm, and this was mostly because of unjustified prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…In India, "inappropriate drug selection" accounted for 20% of DRPs, while in Norway, "no further need for the drug" was the most common DRP. 34,35 Meanwhile, in Ethiopia, "the need for additional drug therapy" was the most common DRP (25.2%). 36 In Jordan, the unique expertise of clinical pharmacists is not introduction of these services in the country, in addition to the lack of institutional policies that define the role and responsibilities of the clinical pharmacist as a healthcare provider.…”
Section: Discussionmentioning
confidence: 99%